(untitled) (Damascus University Journal for legal sciences, 2026)
Many modern management concepts have emerged in recent times, which have received increasing attention from public and private sector institutions for their significant role in developing administrative work and contributing to increasing productivity. One of these concepts is the concept of workers’ administrative empowerment and its reflection on the job satisfaction of workers. Empowerment would break administrative and managerial boundaries, which in turn reflected increased trust between management and employees as a result of giving them decision-making authority and involvement in the management process. and also increases employee satisfaction, which has a significant impact on the effectiveness of workers’ production employment satisfaction ", where job satisfaction is one of the factors leading to a higher performance of employees within institutions. The relationship between workers’ empowerment and job satisfaction is therefore one of dismissal the more workers’ empowerment the more this reflects the greater job satisfaction of workers.